2020
DOI: 10.1186/s12916-020-01540-x
|View full text |Cite
|
Sign up to set email alerts
|

Second and third trimester fetal ultrasound population screening for risks of preterm birth and small-size and large-size for gestational age at birth: a population-based prospective cohort study

Abstract: Background: Preterm birth, small size for gestational age (SGA) and large size for gestational age (LGA) at birth are major risk factors for neonatal and long-term morbidity and mortality. It is unclear which periods of pregnancy are optimal for ultrasound screening to identify fetuses at risk of preterm birth, SGA or LGA at birth. We aimed to examine whether single or combined second and third trimester ultrasound in addition to maternal characteristics at the start of pregnancy are optimal to detect fetuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
(81 reference statements)
1
13
0
1
Order By: Relevance
“…Open access and third trimester US for an estimation of risk of preterm birth (PTB), [7][8][9] to date these measures have not been widely adopted, are subject to user experience and have reported variable performance characteristics. The availability and expertise of US in disadvantaged areas is limited.…”
mentioning
confidence: 99%
“…Open access and third trimester US for an estimation of risk of preterm birth (PTB), [7][8][9] to date these measures have not been widely adopted, are subject to user experience and have reported variable performance characteristics. The availability and expertise of US in disadvantaged areas is limited.…”
mentioning
confidence: 99%
“…Most EFW formulas show a strong correlation between the predicted weight and actual birth weight (r > 0.9, 19/21 formulas) [6]. The area under the curve (AUC) for predictions based on EFW measurements in the mid-trimester or third-trimester ultrasound was 0.69~0.72 and 0.79, respectively [9,10]. The combination of an EFW model in the second and third trimesters along with assessment of maternal factors (MF) and placental ow measurements can improve the screening results for SGA (AUC, 0.84; 95%CI 0.82-0.87) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The area under the curve (AUC) for predictions based on EFW measurements in the mid-trimester or third-trimester ultrasound was 0.69~0.72 and 0.79, respectively [9,10]. The combination of an EFW model in the second and third trimesters along with assessment of maternal factors (MF) and placental ow measurements can improve the screening results for SGA (AUC, 0.84; 95%CI 0.82-0.87) [10]. Ciobanu et al showed that the AUC of EFW measurements was 0.883 at 35 and 36 weeks of gestation, while the AUC for births that occurred within two weeks of the evaluation could be as high as 0.933 [11].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of a first trimester model is to identify the women at risk for severe early phenotype (FGR-I) and to enable early initiation of therapeutic intervention to alter the course the disease, as has been shown in the meta-analysis of nine trails on the use of aspirin (including 1317 women) [67], and a recent large international RCT (Aspre trial) [68]. Conversely, prediction models in the third trimester can help to optimize monitoring and 9 timing of delivery in pregnancies with suspected late FGR-II [69][70][71]. Figure 2 shows a proposed model for screening and follow-up of suspected FGR in each trimester of pregnancy using maternal characteristics (MC), doppler, biometry and biomarker measurements.…”
Section: Gestational Age-dependent Model For Prediction and Management Of Fgrmentioning
confidence: 99%
“…During the third trimester, prediction models generally have better predictive ability due to being temporally closer to the onset of clinical disease. In a prospective population-based cohort among 7,677 pregnant women, the detection of fetuses at risk for adverse birth outcomes nearly doubled, with the implementation of third trimester fetal ultrasound scan, combined with maternal characteristics, compared with only second trimester ultrasound [70]. Prediction models can also be improved because of the composition of the model (addition of biomarkers and/or growth velocity).…”
Section: Third Trimester Prediction and Monitoring Of Fgrmentioning
confidence: 99%